Subramanian, K.A., Rangnekar, P. & Naik, R. (2013) Idionyx (Odonata: Corduliidae) of the Western Ghats with a description of a new species. Zootaxa, 3652 (2), 277–288. - Subramanian, K. A.; Rangnekar, P.; Naik, R. (Zootaxa, 2013)
...